Networking for Peace: A Case Study of the Asian Muslim Action Network (AMAN) - Mohamad Fikri Pido (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2013)
Since its inception in 1990, Asian Muslim Action Network (AMAN) was an endeavor to bring and link all Muslim and non Muslim as well, both individual and groups, in Asia to respond and meet the challenges faced by the community in the region. As a Muslim organization, AMAN bases itself on fundamental Islamic teachings based on the Quran and intra and inter-faith element has been essential in AMAN’s activities for the past 20 years. With this paper, the author examines AMAN’s experience on 3 issues. First, the importance of Islam through its faith based organization to look and work for peace of all mankind. In this part, Islam ‘seems’ universal for peace. Second, meaning of peace. There can be different faces of peace depending on the context we face. Thus, question of ‘what is peace’ needs a modification to be “what does it mean to be Peaceful?” Lastly, the challenges for faith based organization to set up inter-faith cooperation in working toward the mutually desired situation that enables peace to foster. Keywords: faith based organization, peace, conflict, inter-faith cooperation.